PENGARUH STRATEGI GREEN MARKETING TERHADAP PILIHAN KONSUMEN MELALUI PENDEKATAN MARKETING MIX - Feriandy Feriandy (Sekolah Tinggi Manajemen IMMI Jakarta, 2021)
Green Marketing Strategy is a one-way marketing strategy flow that is made to direct someone to buy theproduction produced by the company. Consumer Choice through the marketing mix approach is a reference to thesuccess of a company in providing its services to consumers. The purpose of this research is to find out whether thereis an effect of Green Marketing Strategy on Consumer Choicethrough the Marketing Mix Approach at PT. AskotamaInti Nusantara.“The sampling technique used in this study the author uses the Random Sampling technique(Randomly on All Consumers) where each member of the population has the same opportunity to be selected as theoverall sample, but the sample in this study is the entire population that is sampled .“The results obtained thatpartially and simultaneously there is a positive and significant influence betweenthe Green Marketing Strategy onConsumer Choices Through the Marketing Mix Approach.“Keywords: GreenMarketing Strategy and Consumer Choice Through the Marketing Mix Approach.